O Uso de simulações virtuais em óptica geométrica: uma proposta de sequência didática aplicado ao ensino de Ciências - SANTOS, Ádila Larissa Costa (2023)
The present work, of a bibliographical and theoretical nature, aims to discuss a proposal for a didactic sequence aimed at teaching geometric optics, in the context of Elementary Education, mediated by the use of virtual simulations. This research was developed by the scholarship student linked to the Institutional Program of Scientific Initiation Scholarships (PIBIC), from the public notice 07/2021 – PROPESP, from the Federal University of Pará (UFPA). For the construction of a didactic sequence proposal, aiming to promote a progressive and systematic learning of the teaching of geometric optics, the studies of Zabala (2014) were taken as a basis. It is concluded that the use of virtual simulations can have a great capacity to enable new ways of teaching and learning, actively promoting student interaction in the construction of knowledge within the classroom. In addition, the construction process of the didactic sequence allowed a greater professionalization of the scholarship student in question.